Heterobenzylic C(sp3)─H Acylation of Isoindolinones via Photoinduced Intermolecular Hydrogen Atom Transfer Strategy - Muthuvel, Karthick; Sivaraj, Chandrasekaran; Gandhi, Thirumanavelan (Synlett, 2025)
Heterobenzylic C(sp3)−H functionalization of isoindolinones remains challenging yet highly desirable. Herein, we present a photo-induced hydrogen atom transfer (HAT) strategy for heterobenzylic C(sp3)−H acylation of isoindolinones using acyl azolium salts under mild reaction conditions. This metal-free protocol offers excellent functional group compatibility and avoids the usage of Lewis acids or oxidants, providing a sustainable and efficient approach to C–H acylation.
Keywords: Azolium salts; Photocatalysis; Isoindolinones; Acylation; Radical cross coupling